1969
DOI: 10.1172/jci106176
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucocorticoids on thyrotropin secretion

Abstract: A B S T R A C T The effect of large doses of glucocorticoids on thyrotropin (TSH) secretion in normal and hypothyroid humans has been studied. Plasma TSH concentrations were measured before, during, and after treatment with dexamethasone given orally for 24-48 hr. In 17 patients with primary hypothyroidism, plasma TSH levels fell significantly during treatment to a mean of 54% of control (range 23-96%). Within 48 hr after the withdrawal of dexamethasone, TSH concentrations transiently increased above pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(100 citation statements)
references
References 17 publications
3
95
0
2
Order By: Relevance
“…The effect on thyroid function has been previously described in humans (Wilber and Utiger 1969;Faglia et al 1973;Degroot and Hoye 1976) and in rats (Ranta 1975). The reduction in thyroxine secretion is probably due to a direct action on the pituitary and on the thyroid.…”
Section: Discussionmentioning
confidence: 76%
“…The effect on thyroid function has been previously described in humans (Wilber and Utiger 1969;Faglia et al 1973;Degroot and Hoye 1976) and in rats (Ranta 1975). The reduction in thyroxine secretion is probably due to a direct action on the pituitary and on the thyroid.…”
Section: Discussionmentioning
confidence: 76%
“…The suppressive effects of glucocorticoids upon TSH secretion from the pituitary have been reported by several investigators (Wilber and Utiger, 1969;Nicoloff et al, 1970;Wilber, 1973). They postulated that this suppressive effect might occur by reducing TRH secretion itself.…”
Section: Report Of a Casementioning
confidence: 87%
“…This "corticogenic hypothyroidism" was assumed to be due to the suppressive effect of glucocorticoid on TSH secretion (Wilber and Utiger, 1969 ;Nicoloff et al, 1970). A previous study (Stoica et al, 1966) has reported that laboratory evidence of hypothyroidism was found in over 80% of patients with Cushing's syndrome, although details of plasma hormone levels have not been reported.…”
mentioning
confidence: 99%
“…Glucocorticoids can lower serum TSH concentrations through TRH suppression in the PVN (Alkemade et al, 2005;Wilber & Utiger, 1969). TRH neurons possess glucocorticoid receptors, and a response element to the hormone has been identified in the TRH gene (Cintra et al, 1990).…”
Section: Drugs Affecting Thyroid-stimulating Hormone Secretionmentioning
confidence: 99%